Epidemiology of Pancreatic Carcinoma in Canada: 1931 to 1985 - Anthony Ayiomamitis (Canadian Journal of Gastroenterology)
Pancreatic carcinoma accounts for approximately one of every 20 deaths from cancer and one out of every 30 new cases of cancer in Canada. It is among the 10 leading causes of death from cancer and the 10 leading sites of newly diagnosed cases for a number of age groups. Age standardized mortality rates have risen sharply in both males (2.0 to 9.5 deaths per 100,000 population per year) and females (2.2 to 5.7 deaths per 100.000 population per year) during 1931 ro 1985 (P < 0.0001). The increase in standarized rates, 0.14 and 0.07 additional deaths per 100,000 population per year in males and females, respectively, is attributable to significant increases in age specific rates for males and females aged 35 to 44, 45 to 54, 55 to 64, 65 to 74, 75 co 84 and over 85 years old ( P ≤ 0.0005) in whom rates have risen by as much as 2.5 additional deaths per 100,000 population per year. Although age standardized incidence rnte5 have risen marginally in males (P = 0.085), age specific rates in males aged 0 to 24 years have risen significantly (P = 0.01 ). In contrast, standarized incidence races have risen sharply in females (0.12 additional new cases per 100,000 population per year; P = 0.0007), which was also characteristic of age specific rates for women aged 45 to 54, 55 ro 64, 65 to 74 and 75 to 84 years old (P < 0.03) where rates have risen by 0.15 to 1.65 additional new cases per 100,000 population per year. Recent age specific incidence and mortality rates indicate that morbidity and mortality rates rise sharply after age 45, when rates double between successive 10-year age groups, and peak for males and females aged more than 85 years.